Pengaruh Metode Eksperimen Terhadap Kemandirian Belajar Siswa Kelas IV Mata Pelajaran IPA SD Negeri 4 Metro Utara - Maharani, Winda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
This research is based on the low learning independence of these students, ultimately causing students to be less careful in determining learning goals, determining learning resources, and determining learning strategies from the learning they have done. This research was conducted in connection with the use of experimental methods in natural science subjects at SD Negeri 4 Metro Utara especially in grade IV students. The purpose of this research is to increase the independence of student learning,especially in material related to the properties of light in natural science subjects. This type of research is a quasi-experimental study using nonequivalent groups pre-test-post test design. The subjects in this study were fourth grade students at SD Negeri 4 Metro Utara. Data collection techniques in the form of direct observation and student questionnaire responses. The research instrument was in the form of anindependent learning observation sheet and a student questionnaire response sheet. The results of this study indicate that the use of experimental methods in natural science subjects can improve the learning independence of fourth grade students of SD Negeri 4 Metro Utara. This can be seen from the increase in the number of values on each indicator of learning independence observed. The results of this study can be a suggestion for teachers and schools to continue to vary the science learning with appropriate methods, especially experimental methods, so as to increase student learning independence.